1997
DOI: 10.1021/ie970120o
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Adsorption of 1,1-Dichloro-1-fluoroethane by Various Adsorbents

Abstract: Experiments have been conducted to examine the liquid-phase adsorption/desorption characteristics of 1,1-dichloro-1-fluoroethane (HCFC-141b) by activated alumina, molecular sieve, granular activated carbon (GAC), extruded activated carbon (EAC), and activated carbon fiber (ACF). HCFC-141b is currently regarded as an excellent replacement for CFC-11, a foaming agent widely used in the rigid polyurethane foam industries. The experimental results of adsorption and desorption were analyzed in terms of the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These equations are the Langmuir, Freundlich, Sips, Toth, and Dubinin−Radushkevich equations. , The Langmuir isotherm equation is and the Freundlich isotherm is where q e is the amount adsorbed, q m and b are Langmuir's parameters, A and n are the Freundlich parameters, and C e is the equilibrium concentration. Those equations are the most widely used to correlate liquid-phase adsorption data. ,, In a number of studies, these two equations failed to describe the liquid-phase adsorption data. ,,, Both of these equations also give unsatisfactory result for correlation of our experimental data, as indicated in Figure . The Langmuir and Freundlich parameter values for benzene and toluene obtained from our adsorption experiment are summarized in Table .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These equations are the Langmuir, Freundlich, Sips, Toth, and Dubinin−Radushkevich equations. , The Langmuir isotherm equation is and the Freundlich isotherm is where q e is the amount adsorbed, q m and b are Langmuir's parameters, A and n are the Freundlich parameters, and C e is the equilibrium concentration. Those equations are the most widely used to correlate liquid-phase adsorption data. ,, In a number of studies, these two equations failed to describe the liquid-phase adsorption data. ,,, Both of these equations also give unsatisfactory result for correlation of our experimental data, as indicated in Figure . The Langmuir and Freundlich parameter values for benzene and toluene obtained from our adsorption experiment are summarized in Table .…”
Section: Resultsmentioning
confidence: 96%
“…Adsorption onto activated carbon provides a feasible technique and is one of the most extensively used technologies for removal of organic pollutants from industrial wastewater. As one of the most important pieces of information in analysis and design of adsorption separation processes, liquid-phase adsorption isotherm data of various organic compounds in several systems have been obtained by various investigators and have been reported in different places over the years. …”
Section: Introductionmentioning
confidence: 99%
“…The pseudo-firstorder equation was used extensively to describe the sorption kinetics [15][16][17][18][19]33,34]. Another model for the analysis of sorption kinetics is pseudo-second-order.…”
Section: Theorymentioning
confidence: 99%
“…Ion chromatography analysis showed that the desulfurized components were not converted to the sulfate anion, and thus were possibly converted to aromatic sulfate anion form. Aluminum oxide and activated carbon are used in most cases as adsorbents for highly polarized compounds in nonpolar solvents and also for organic components in aqueous solutions …”
Section: Resultsmentioning
confidence: 99%
“…Aluminum oxide and activated carbon are used in most cases as adsorbents for highly polarized compounds in nonpolar solvents 17 and also for organic components in aqueous solutions. 18 The DBT/tetradecane and 10% H 2 O 2 solutions were mixed and photoirradiated for 20 h and the aqueous phase was recovered. The aqueous phase was introduced to the top of the column, containing 5 g of adsorbents, and the eluted fractions (10 mL) were analyzed.…”
Section: Effect Of Benzophenone and Hydrogen Peroxide On The Desulfur...mentioning
confidence: 99%